2009
DOI: 10.1002/jemt.20764
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical characterization of TH13‐L2 spinal ganglia neurons in sheep (Ovis aries)

Abstract: Spinal ganglia (SG) neurons are commonly classified according to various specific features. The most widespread classification based on morphological and ultrastructural features subdivides SG neurons into light and small dark neurons. Using immunohistochemical, histochemical and lectin methods, it is possible to further subdivide the small dark neurons into two subpopulations: peptidergic and nonpeptidergic neurons. The majority of studies on SG neurons were carried out on mice and rats; there are few or no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 47 publications
12
29
0
Order By: Relevance
“…Most IB41 fibers were unmyelinated, and about 5% were small myelinated, corroborating previous electrophysiological (Gerke and Plenderleith, 2001;Fang et al, 2006) and LM immunohistochemical (Wang et al, 1994;Russo et al, 2010) evidence in the DRG. Previous EM studies in the peripheral nerve and the spinal cord reported that IB4 is expressed exclusively in unmyelinated fibers (Streit et al, 1986;Kitchener et al, 1993;Murinson et al, 2005), possibly because of loss of myelin sheath in the IB41 myelinated fibers in the periphery.…”
Section: Neuronal Marker Expression In Sensory Rootsupporting
confidence: 89%
“…Most IB41 fibers were unmyelinated, and about 5% were small myelinated, corroborating previous electrophysiological (Gerke and Plenderleith, 2001;Fang et al, 2006) and LM immunohistochemical (Wang et al, 1994;Russo et al, 2010) evidence in the DRG. Previous EM studies in the peripheral nerve and the spinal cord reported that IB4 is expressed exclusively in unmyelinated fibers (Streit et al, 1986;Kitchener et al, 1993;Murinson et al, 2005), possibly because of loss of myelin sheath in the IB41 myelinated fibers in the periphery.…”
Section: Neuronal Marker Expression In Sensory Rootsupporting
confidence: 89%
“…The anti-nNOS antibody (Santa Cruz Biotechnology, Santa Cruz, CA; (A-11) sc-530) employed in this study was tested in a double-staining protocol with a polyclonal anti-nNOS antibody raised against amino acids 1414-1434 of human nNOS (Biomol, Plymouth Meeting, PA; SA227). The two antibodies showed a full correspondence, with the same fibers and neurons stained, as recently shown on sheep DRG (Russo et al, 2010).…”
Section: Antibody Characterization Specificity Of Primary Antibodiessupporting
confidence: 64%
“…In this study, immunoperoxidase and double immunofluorescence techniques were used to determine the distribution and the number of nitrergic neurons in the DRGs. As nitrergic neurons of the DRGs contain tachykinins (Aimi et al, 1991;Zhang et al, 1993;Ruscheweyh et al, 2006;Tan et al, 2008;Russo et al, 2010) in others mammals, double immunofluorescence was used to determine if nNOS is colocalized with SP also in Tursiops truncatus.…”
mentioning
confidence: 99%
“…NO regulates many functions in the DRGs, including transmission of visceral sensation, primary afferent neurons development and differentiation, communication between neurons and satellite glial cells, and neuroprotection (Aimi et al, 1991;Thippeswamy and Morris, 2002;Tan et al, 2008;Russo et al, 2010). In addition, immunohistochemical, electrophysiological, and pharmacological studies have suggested that NO acts as a neu-rotransmitter or neuromodulator in the processing of nociceptive stimuli.…”
mentioning
confidence: 99%